"It's Doable": International Graduate Students' Perceptions of Online Learning in the U.S. During the Pandemic. (May 2022) - Han, Yesul; Chang, Yunjeong; Kearney, Erin
This study aims to understand the learning experiences and challenges of international students enrolled in Master's and PhD programs in various institutions who were forced to transition to online learning during the pandemic. In particular, the study explores the experiences and perceptions of seven non-native English-speaking international graduate students who came from six different countries and studied at different schools of education through phenomenological interviews. Analysis yields insight into these students' online learning experiences and identifies factors which contributed to the mixed quality of these learning experiences. Overall, students tried to adapt to the "new normal, " while enduring learning and emotional challenges due to the harsh conditions of the pandemic in the United States and their home countries. Instructors' readiness for online teaching as well as the extra support provided to help students cope with the sudden transition in the learning environment were particularly important factors affecting the students' learning experiences. Our findings lead us to several recommendations for practice within graduate-level online learning environments and suggestions for further research, as well as broader considerations of what broader implications the case suggests for international education in light of digitalization.